Herthadalen, fortidsbruk og historiefag - Eriksen, Anne (Historisk Tidsskrift, 2019)
Herthadalen – uses of the past and the discipline of history In his now-classic book Theatres of Memory, Raphael Samuel states that ‘if history was thought of as an activity rather than a profession, then the number of practitioners would be legion.’ Looking beyond history as academic work carried out by professionals trained in specific scholarly methods, he claimed, makes it possible to catch sight of other agents who investigate, interpret and care about the past for other reasons and by different means. The present article argues that however inspiring this appeal might be, it is fundamentally based on the existence of the very profession that it wants to see beyond. Taking the rebuilding and redecorating of Ledreborg manor and park during the second half of the 18th century as its case, the article examines the uses of history before its development into a modern research discipline created the distinction between profession and activity. This is not to say that the use of history in the 18th century was more ‘democratic’, but rather that it rested on other kinds of authority and could fill other social and cultural roles. In consequence, a far larger number of persons, positions and professions involved in the construction and use of Ledreborg manor and gardens can be identified and examined, unrestrained by the more recent distinctions between (real) history and its Others. More theoretically, the perspective invites considerations about how modern notions of history shape the way professional historians approach the past.